Higher expression of BRCA1, and CHUK and lower expression of NFKBIA, ESR1, PIK3R1, and PPARG in HAM/TSP compared to ATLL, a diverse pathological consequence - Sahar Yaslianifard; Monireh Movahedi; Somayeh Yaslianifard; Sayed-Hamidreza Mozhgani (Indian Journal of Pathology and Microbiology)
Background: HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP) and adult T-cell leukemia/lymphoma (ATLL) are both severe diseases caused by Human T-lymphotropic virus type 1 (HTLV-1) infection, while about 95% of infected cases remain asymptomatic. Genes that play a role in ATLL development are assumed to be dissimilar from the ones that are crucial factors for HAM/TSP occurrence. Objective: The expression of six genes including BRCA1, CHUCK, ESR1, NFKBIA, PIK3R1, and PPARG were assessed in two groups of HAM/TSP and ATLL patients. Materials and Methods: cDNA was synthesized from purified RNA, and RT-qPCR was conducted to assess the expression of the genes in two groups. Any possible correlation among the genes’ expression was also calculated. Results: BRCA1 and CHUCK expressions were higher in HAM/TSP patients in comparison with ATLL patients. However, ESR1, NFKBIA, PIK3R1, and PPARG are more expressed in ATLL cases than HAM/TSP. A significant positive correlation was observed between BRCA1 and NFKBIA in HAM/TSP group. In addition, a significant negative correlation between PIK3R1 and PPARG in HAM/TSP and between ESR1 and NFKBIA in the ATLL group was obtained. Conclusion: HAM/TSP or ATLL stem from a disturbance in the expression of diverse genes and these dissimilarities should be discovered to reach a better understanding of disease treatment as well as screening and assessing the asymptomatic carriers’ condition for developing severe disease.